2016
DOI: 10.1055/s-0035-1561644
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses towards the Strengthening of Cyclopropene Chemistry

Abstract: This short review focuses on the most relevant achievements in the field of cyclopropene chemistry including their syntheses, reactivities, and applications. As the chemistry of cyclopropenes has rapidly evolved in the last few years, valuable implementations on synthetic approaches are nowadays available. Moreover, exciting and useful applications by means of cyclopropenes in organic synthesis and other research areas have also been disclosed. Herein, an overview covering advances accomplished from 2011 until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…As an alternative strategy, non-diazo carbene precursors have attracted considerable interest over the last decades (Jia and Ma, 2016, Ma et al., 2016, Wang and Wang, 2019). Cyclopropene, a reliable and easy-to-handle precursor, could generate vinyl carbene in a safe, mild, and practical way with a 100% atom economy via transition metal-catalyzed ring-opening rearrangement (Rubin et al., 2007, Archambeau et al., 2015, Vicente, 2016, Benitez et al., 2009). Furthermore, the unique vinyl functionality could offer new opportunities to discover new transformations.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative strategy, non-diazo carbene precursors have attracted considerable interest over the last decades (Jia and Ma, 2016, Ma et al., 2016, Wang and Wang, 2019). Cyclopropene, a reliable and easy-to-handle precursor, could generate vinyl carbene in a safe, mild, and practical way with a 100% atom economy via transition metal-catalyzed ring-opening rearrangement (Rubin et al., 2007, Archambeau et al., 2015, Vicente, 2016, Benitez et al., 2009). Furthermore, the unique vinyl functionality could offer new opportunities to discover new transformations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the use of alternative vinyl carbene precursors is highly desirable to expand the accessibility to 1,2-divinylcyclopropanes [1719]. In this regard, cyclopropenes have demonstrated to be suitable precursors of metal–vinyl carbenes [2021], which can be easily trapped with alkenes [2225]. Our recent studies showed that simple ZnCl 2 could be used to generate the corresponding zinc–vinyl carbene to efficiently prepare vinylcyclopropane derivatives with a remarkable broad scope (Scheme 1) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in base-assisted additions of heteroatom-based nucleophiles to cyclopropenes made available novel stereo-defined cyclopropyl scaffolds, 1 possessing oxygen, 2 nitrogen, 3 sulfur, 4 or halogen 5 entities, that complement transition-metal-catalyzed cyclopropanation methodologies. 6,7 Both intermolecular (Scheme 1, eq 1) and intramolecular (Scheme 1, eq 2) addition of tethered nucleophiles, employing carbon- 8 or oxygen-based species, has been reported.…”
Section: Introductionmentioning
confidence: 99%